Creative tourism special issue - foreword - João Filipe Marques; Alexandra Rodrigues Gonçalves; Sónia Moreira Cabeça; Mirian Tavares (Tourism & Management Studies)
First developed in 2000 by Richards and Raymond (2000), the concept of creative tourism is now relatively stabilised and broadly used in research on cultural tourism’s emergent modalities (Gonçalves, 2008). According to its initial conceptualisation, creative tourism implies tourists’ active participation in learning experiences that stimulate the development of their ‘creative potential’. The concept’s growing use is related to two significant contemporary societal trends. The first is a shift from ‘mass cultural tourism’ to an increased interest in authentic ‘everyday life’ in destinations (Guerreiro & Marques, 2017). The second trend is cultural changes that have been designated as ‘the creative turn’ (e.g. an insistence on the ‘rhetoric of creativity’). Cities must be creative in order to attract not only tourists but also ‘creative industries’ (Tavares, 2014, 2015) and ‘creative classes’ (Cruz, 2016; Florida, 2003). Tourism destinations and experiences and tourists themselves must be in some way ‘creative’, that is, be immersive, interactive and meaningful.